Pengetahuan dan Sikap Remaja Putri tentang Pencegahan Keputihan (Flour Albus) di SMA N 7 Kota Jambi - Sinulingga, Selpyani; Jayanti, Ova (3031-8572, 2024)
Data from the World Health Organization (WHO) states that, in 2021, the prevalence rate of women in Indonesia who experienced vaginal discharge was 75% with the occurrence of vaginal discharge at least once in their lives, then 45% of women experienced vaginal discharge more than twice. Women in Indonesia who experience vaginal discharge are 90% with 60% of them experienced by adolescent girls. About 90% of women in Indonesia have the potential to experience vaginal discharge because Indonesia is a tropical climate, so fungi are easy to develop which results in many cases of vaginal discharge. Symptoms of vaginal discharge are also experienced by unmarried women or adolescent girls aged 15-24 years, which is around 31.8% and has increased every year. This research was conducted at SMA N 7 Jambi City in September 2023 to August 2024, with the aim of the study to determine the description of knowledge and attitudes of adolescents about the prevention of vaginal discharge. This research is quantitative with a descriptive approach. Data collection of knowledge and attitudes of adolescents about the prevention of vaginal discharge was collected by questionnaire. The population in this study were all adolescent girls in SMA N 7 Jambi City, totaling 255 people with a sample of 72 people. The sampling technique was Proportional random sampling. Data analysis was done univariately. The results showed that the majority of adolescents' knowledge was still lacking (41.67%) and had a negative attitude (69.44%) towards preventing Flour Albus. From the results of this study, it is hoped that health workers and midwifery service providers as well as schools will be more active in providing education to adolescent girls about Flour Albus and its prevention. The research output is publication in an Accredited National Journal.